Polliniferous structures in typical bees - Meyer, Frederick Hugo (My University, 1897)
Introduction: We pass by the blooming plants of spring and summer, such as the plum crabapple, locust and spiraea and hear the never ceasing hum of the industrious bee, but we seldom think of their place in nature, and the important function they perform in the plant kingdom. The bee while visiting the flowers in search of honey and pollen as food for its young and itself, unknowingly accomplishes another purpose; it carries pollen from the anthers of one flower to the stigma of another, accomplishing the process of cross-fertilization, which through a well known law, strengthens the species for a battle among surrounding species. A case of “the survival of the fittest.” The honey bee is widely known to mankind through its wonderful assiduity and skill in collecting and storing of honey, producing an economic product. And for this product they have been studied and guarded from time immemorial. Indeed many operations of this little instinct are so complex as to induce a suggestion of reasoning in their procedure, instead of working blindly to an end.
Citation: Meyer, Frederick Hugo. Polliniferous structures in typical bees. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Entomology; Physiology; Honey bees; Bees; Theses; Manuscripts (documents)